2019
DOI: 10.1212/nxi.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Cranial nerve involvement in patients with MOG antibody–associated disease

Abstract: ObjectiveTo describe clinical and radiologic features of cranial nerve (CN) involvement in patients with myelin oligodendrocyte glycoprotein antibodies (MOG-IgG) and to assess the potential underlying mechanism of CN involvement using a nonhuman primate (NHP) model.MethodsEpidemiologic, clinical, and radiologic features from a national cohort of 273 MOG-IgG–positive patients were retrospectively reviewed for CN involvement between January 2014 and January 2018. MOG-IgG binding was evaluated in CNS, CN, and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…Interestingly, for MOG-antibody-associated disease, besides NMO phenotype, optic neuritis, and myelitis, some of these MOG-antibody-positive cases also have clinical phenotypes beyond the current NMOSD spectrum, such as ADEM/MDEM-like presentation ( 71 ), cerebral cortical encephalitis ( 12 ), and cranial nerve involvement ( 14 ). Pathologically, MOG-antibody-associated disease is a type of demyelinating disease, as opposed to astrocytopathic disease seen in AQP4-antibody-positive NMOSD ( 72 , 73 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, for MOG-antibody-associated disease, besides NMO phenotype, optic neuritis, and myelitis, some of these MOG-antibody-positive cases also have clinical phenotypes beyond the current NMOSD spectrum, such as ADEM/MDEM-like presentation ( 71 ), cerebral cortical encephalitis ( 12 ), and cranial nerve involvement ( 14 ). Pathologically, MOG-antibody-associated disease is a type of demyelinating disease, as opposed to astrocytopathic disease seen in AQP4-antibody-positive NMOSD ( 72 , 73 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two of these patients showed gadolinium enhancement of the trigeminal nerve at the transitional zone, which contains an overlap of central and peripheral myelin features at the root level. In contrast, the remaining patient had an oculomotor nerve involvement at the root exit and the cisternal level that showed gadolinium enhancement that extended beyond the anticipated transitional zone between peripheral and central myelin . Vazquez Do Campo et al reported a patient with combined central and peripheral demyelination syndromes with elevated serum MOG IgG1 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…MOG-IgG+ patients with clinical and neuroimaging characteristics of NMOSD are currently discussed as a different disease entity (17)(18)(19)(20)(21)(22)(23). Cortical encephalitis and seizures or cranial nerve involvement have also been reported in MOG-IgG+ patients (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%